(untitled) (Praxis Educativa, 2023)
The complexity that citizen education spaces owe to their multidisciplinary nature makes the study of disciplinary conceptions that underlie curricular developments relevant. In this sense, the present work proposes to analyze the curricular definitions on education for citizenship at the secondary level from a comparative study of the jurisdictions of the City of Buenos Aires and the Province of Buenos Aires. In particular, the conceptions of law that underlie the curricular designs of each jurisdiction will be investigated, taking into account the different levels of government of the educational system and the articulation of jurisdictional and national initiatives at the federal level.